Arthroscopic Anatomic Glenoid Reconstruction Without Subscapularis Split - Ivan H. Wong, M.D., M.Sc., F.R.C.S.C., Dip. Sports Medicine; Nathan Urquhart, M.D., M.Sc., F.R.C.S.C., Dip. Sports Medicine (Arthroscopy Techniques, 2015)
The role of bone loss from the anterior glenoid in recurrent shoulder instability has been well established. We present a completely arthroscopic technique for reconstructing the anterior glenoid with distal tibial allograft and without a subscapularis split. We perform the arthroscopy in the lateral position. We measure and size an allograft distal tibial graft and place it arthroscopically. We use an inside-out medial portal to introduce the graft into the shoulder, passing it through the rotator interval and above the subscapularis. A double-cannula system is used to pass the graft, which is temporarily fixed with K-wires and held in place with cannulated screws. We then perform a Bankart-like repair of the soft tissues to balance the shoulder and augment our repair. Our technique is not only anatomic in the re-creation of the glenoid surface but also anatomic in the preservation of the coracoid and subscapularis tendon and repair of the capsulolabral complex.